The Important Interface Between Apolipoprotein E and Neuroinflammation in Alzheimer’s Disease - Kloske, Courtney M.; Wilcock, Donna M. (Frontiers in Immunology, 2020)
Alzheimer’s disease (AD) is the most prevalent form of neurodegenerative disease, currently affecting over 5 million Americans with projections expected to rise as the population ages. The hallmark pathologies of AD are Aβ plaques composed of aggregated beta-amyloid (Aβ), and tau tangles composed of hyperphosphorylated, aggregated tau. These pathologies are typically accompanied by an increase in neuroinflammation as an attempt to ameliorate the pathology. This idea has pushed the field toward focusing on mechanisms and the influence neuroinflammation has on disease progression. The vast majority of AD cases are sporadic and therefore, researchers investigate genetic risk factors that could lead to AD. Apolipoprotein E (ApoE) is the largest genetic risk factor for developing AD. ApoE has 3 isoforms-ApoE2, ApoE3, and ApoE4. ApoE4 constitutes an increased risk of AD, with one copy increasing the risk about 4-fold and two copies increasing the risk about 15-fold compared to those with the ApoE3 allele. ApoE4 has been shown to play a role in Aβ deposition, tau tangle formation, neuroinflammation and many subsequent pathways. However, while we know that ApoE4 plays a role in these pathways and virtually all aspects of AD, the exact mechanism of how ApoE4 impacts AD progression is murky at best and therefore the role ApoE4 plays in these pathways needs to be elucidated. This review aims to discuss the current literature regarding the pathways and mechanisms of ApoE4 in AD progression with a focus on its role in neuroinflammation.